2005
DOI: 10.1093/brain/awh711
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological sequelae of bacterial and viral meningitis

Abstract: Survivors of meningitis often complain about neurological and neuropsychological consequences. In this study, the extent of these sequelae was quantified and correlated to MRI findings. Neurological, neuropsychological and neuroradiological examinations were performed with adult patients younger than 70 years, 1-12 years after recovery from bacterial meningitis (BM; n = 59), or from viral meningitis (VM; n = 59). Patients with other potential causes for neuropsychological deficits (e.g. alcoholism) were carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 40 publications
(49 reference statements)
9
111
0
5
Order By: Relevance
“…27 Cognitive deficiencies after bacterial and viral meningitis (predominantly shortterm and working memory) also have been described. 28 Although impaired cognition related to CM infection, ranging from acute confusion, psychosis, and mania to encephalopathy, is well known, evidence is based on case reports [29][30][31][32] or comorbidity with HIV infection. 33 This is the first study to show correlations between neuropsychologic sequelae and changes in DTI parameters in patients with HIV-negative CM by measuring DTI parameters.…”
Section: Discussionmentioning
confidence: 99%
“…27 Cognitive deficiencies after bacterial and viral meningitis (predominantly shortterm and working memory) also have been described. 28 Although impaired cognition related to CM infection, ranging from acute confusion, psychosis, and mania to encephalopathy, is well known, evidence is based on case reports [29][30][31][32] or comorbidity with HIV infection. 33 This is the first study to show correlations between neuropsychologic sequelae and changes in DTI parameters in patients with HIV-negative CM by measuring DTI parameters.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent German study evaluating cognitive outcome 1 to 12 years after bacterial meningitis found a much higher rate of cognitive impairment (37%). 33 These differences are explained by different criteria for cognitive dysfunction. The German study used less strict criteria, resulting in impaired cognitive functioning of the control subjects ranging from 7 to 27% per domain.…”
Section: Discussionmentioning
confidence: 99%
“…From a neuropsychological point of view, the hippocampal predominance of volume loss might explain a considerable part of the memory dysfunctions that survivors of BM often experience. 11,15,16 In our previous study in the same cohort, 11 we found significantly worse neuropsychological performance in BM for working memory, executive, and visoconstructive functions.…”
Section: Discussionmentioning
confidence: 46%
“…From the 58 patients of our previous, retrospective cohort study 11 who had undergone a volumetric MR imaging scan, we excluded those with visible morphologic alterations (12/58). In 5 patients the original DICOM datasets were not available or had quality problems (eg, movement artifacts).…”
Section: Patientsmentioning
confidence: 99%